INFLUENCE OF ENEMY AND FRIENDSHIP ON MEGAMIND'S PERSONALITY IN TOM MCGRATH'S MEGAMIND (2010): A BEHAVIORIST APPROACH - MUSTAQIM, RULIK (2011)
The study is to reveal how the influence of enemy and friendship of the major characters, Megamind. The objective of the study is to analyze the movie based on the structural analysis and the behaviorist approach. This study is a qualitative study. The object of the study is Tom McGrath's Megamind. The data sources are divided into two, namely primary data source and secondary data source. In collecting the data, the writer watches the movie and uses library research by collecting and selecting the appropriate data from many sources. The technique of the data analysis, the writer uses descriptive technique. After analyzing the movie of Tom McGrath's Megamind, the writer concluded that there are several aspects of behaviorist theory of the major character. The aspects consist of positive and negative reinforcement on Megamind's personality and the source of behavior on Megamind's personality that consist of environment, modeling and learning process. Megamind has integrity and he will always be evil and fights the good. But, his nature of being evil can be changed because of the influences of environment, modeling or imitating other and shaping personality through learning the other where he lives. That what makes Megamind from being evil turns to be a good person and he feels more comfortable in his new life.